Guru Dalam Pembentukan Sikap Pluralisme: Penelitian di SMP Cinta Kasih Tzu Chi, Jakarta Barat - Supriyanti, Eka; Safitri, Desy; Saipiatuddin, Saipiatuddin (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2019)
This study aims to (1) Know why teachers must form a pluralism attitude in students in West Jakarta's Tzu Chi Loving Middle School? (2) How do teachers shape pluralism in the Tzu Chi Loving Middle School? provide an overview of the teacher in forming a pluralism attitude at the Cinta Tzu Chi Middle School, West Jakarta. The research method used is descriptive, with data collection techniques through closed questionnaires (questionnaires), observation, interviews and documentation. The subject of this study was the Tzu Chi love junior high school teacher and the Tzu Chi Loving Middle School Student. The results showed that (1) the Tzu Chi Loving Middle School is a school that has religion, as the spearhead in the world of education, teachers have a significant role in the process of developing, directing, and motivating students to become useful human beings for the nation and state . (2) How the teacher in forming the pluralism attitude of students can be seen from how the teacher makes planning and learning processes in the classroom, such as at the beginning the teacher gives advice and motivational sentences to students, then by using the learning method. However, both schools play an important role in the formation of pluralism in the Tzu Chi Loving Middle School so that the process of forming pluralism in diverse schools can work well. Keywords: Pluralism, Tzu Chi Loving Middle School, Tolerance